Pengaruh Modal Intelektual dan Pengungkapan Tanggung Jawab Sosial Perusahaan Terhadap Kinerja Pasar dengan Kualitas Tata Kelola Perusahaan (Studi Empiris pada Perusahaan Jasa Perbankan) - Nazira, Cut; Murni, Murni; Abqa, Rizkan (Singkite Journal, 2024)
This research analyzes the influence of intellectual capital and disclosure of corporate social responsibility on market performance and the quality of corporate governance. Case data for 2015-2021 in the IICG (Institute for Corporate Governance) assessment. This is quantitative research, with a sample of 28 data from 4 companies, using a purposive sampling method. The analysis technique uses multiple linear regression with Moderated Regression Analysis (MRA). The results of the research show that: Intellectual Capital has no effect on market performance. Disclosure of corporate social responsibility has no effect on market performance. The quality of corporate governance as a moderating variable weakens the relationship between intellectual capital and market performance. The quality of corporate governance as a moderating variable weakens the relationship between corporate social responsibility and market performance